Determining an interpretational framework based on a proposed structure for Psalm 47 - Schader, Jo-Mari (Journal for Semitics, 2013)
The problematic structure of Psalm 47, on which there is no consensus, comes under scrutiny in this study as it makes interpretation of some key themes in the psalm difficult. The main concern of this study is an analysis that will determine a working structure as the structure would in turn form the framework for the socio-historical interpretation of the text. The objective of this study is to determine a structure based on an analysis that takes as its point of departure the poetic techniques found within the psalm, followed by a syntactical, stichometric, and structural analysis of the poem. The poetic techniques within the psalm will be emphasised as they are key to understanding the structural layout of the poem.
paid